"Beyond the Clouds": Insider Perceptions on the Transmutation of Terrestrial Radio In Canada - Manchester, Geoffrey W (Université d'Ottawa / University of Ottawa, 2012)
The aim of this study is to understand how leaders in the Canadian radio industry perceive the nascent personalized music streaming service industry, and how those perceptions inform their current business decisions. Over the last few years, Internet-based music services like Deezer and Rdio have launched in Canada, providing listeners with the opportunity of an alternative music experience to conventional broadcast radio. Through five interviews with experts representing terrestrial radio, on-demand services and regulation, three scenarios are presented for the future of conventional radio. In addition, a conceptualized listener profile is created using Grounded Theory Method. This profile buttresses the central finding of this research: should key political, economic and social factors remain in place, conventional radio is likely to continue to dominate as the leading commercial audio platform for Canadians in the years to come.
Keywords: Radio; Music; streaming; new media; Canada